Distribution and Risk Factors of Human Cystic Echinococcosis in Aysén 2010-2016 [Distribución y Factores de Riesgo de Equinococosis Quística Humana en Aysén 2010-2016] - Martinez-Gallegos, P (Sociedad Chilena de Infectologia, 2021)
Background: In Chile, cystic echinococcosis is endemic throughout the country and hyperendemic in some regions such as La Araucanía and Aysén and continues to be a neglected public health problem. Aim: To estimate the risk of human hydatidosis in Aysén, studying the relationship of notifications and hospital discharge rates with social and environmental factors, such as population, multidimensional poverty index, urbanization, average temperature, average rainfall and sheep population. Methods: Poisson regressions were used to study the factors associated with notifiable diseases and hospital discharge rates and the Besag-York-Mollie model for relative risk. Results and Conclusions: Aysén has a high risk, between 2 and 19 times that expected for the region. A significant underreporting of cases was found. The model of hospital discharges had a good fit showing the positive influence of the human and bovine population and the positive effect of temperature. An effect of the multidimensional poverty index was also detected, which is mainly affected by education and working conditions. Excepting one locality, the areas of greatest risk correspond to the eastern cordon of the Aysén region. © 2021, Sociedad Chilena de Infectologia. All rights reserved.